The First Experience of Reproductive Function Restoration in Patients with Asherman's Syndrome Using Autologous Mesenchymal Stem Cells - Kozub, Mykola; Kozub, Maksym; Skybina, Kseniia (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):296